Efficacy and safety of naotaifang capsules for hypertensive cerebral small vessel disease: Study protocol for a multicenter, randomized, double-blind, placebo-controlled clinical trial - Fang, Rui; Hu, Hua; Zhou, Yue; Wang, Shanshan; Mei, Zhigang; She, Ruining; Peng, Xiwen; Jiang, Qiling; Wang, Xiangyuan; Xie, Le; Lin, Hongyuan; Meng, Pan; et al. (Frontiers in Pharmacology, 2023)
Aim of the study:To evaluate the efficacy and safety of NTF capsules on hypertensive cerebral small vessel disease (HT-CSVD). Methods: This study is a multicenter, randomized, double-blind, placebo-controlled clinical trial. A total of 400 patients were recruited from the First Hospital of Hunan University of Chinese Medicine, Hunan Academy of Traditional Chinese Medicine Affiliated Hospital, the First Hospital of Shaoyang University, the First Traditional Chinese Medicine Hospital of Changde, and Jiangmen Wuyi Hospital of Traditional Chinese Medicine between July 2020 and January 2022. After a 4-week run-in period, all participants were divided into the intervention group (represented by Y-T, N-T) and control group (represented by Y-C, N-C); using a stratified block randomized method based on the presence or absence of brain damage symptoms in HT-CSVD patients (represented by Y and N). The Y-T and N-T groups were administered different doses of NTF capsules, whereas Y-C and N-C groups received placebo treatment. These four groups received the treatments for 6 months. The primary outcome included Fazekas scores and dilated Virchow-robin spaces (dVRS) grades on magnetic resonance imaging (MRI). The secondary outcomes included the number of lacunar infarctions (LI) and cerebral microbleeds (CMB) on MRI, clinical blood pressure (BP) level, traditional Chinese medicine (TCM) syndrome scores, mini-mental state examination (MMSE) scale, and safety outcomes. Fazekas scores, dVRS grades, and the number of LI and CMB on MRI were tested before enrollment and after 6 months of treatment. The clinical BP level, TCM syndrome scores, MMSE scale and safety outcomes were tested before enrollment, after 3-month, 6-month treatment and 12th-month follow-up respectively. Conclusion: The protocol will comfirm whether NTF capsules reduce Fazekas scores, dVRS grades, and the number of LI and CMB, clinical BP, increase MMSE scores, TCM syndrome scores of Qi deficiency and blood stasis (QDBS), and improve the quality of life of patients. The consolidated evidence from this study will shed light on the benefits of Chinese herbs for HT-CSVD, such as nourishing qi, promoting blood circulation and removing blood stasis, and dredging collaterals. However, additional clinical trials with large samples and long intervention periods will be required for in-depth research.